The Native Ant Lasius niger Can Limit the Access to Resources of the Invasive Argentine Ant - Marion Cordonnier; Olivier Blight; Elena Angulo; Franck Courchamp (Animals, 2020)
Within ant communities, the biotic resistance of native species against invasive ones is expected to be rare, because invasive species are often highly dominant competitors. The invasive Argentine ant (Linepithema humile (Mayr)) often demonstrated numerical dominance against its opponents, increased aggressiveness, and ability to quickly recruit to food. The present study aimed to assess the behavioral mechanisms involved in the interspecific competition between L. humile, facing either an invasive species (Lasius neglectus Van Loon, Boomsma and Andrásfalvy) or a native dominant species (Lasius niger (Linnaeus)). The resource exploitation by the Argentine ant was investigated during one-hour competitive interactions using 10 dead Drosophila flies as prey. When facing La. niger, L. humile exploratory behavior was strongly inhibited, it brought very few prey resources, and killed few opponents. Conversely, La. neglectus had a low impact on L. humile. Contrarily to expectations, the invasive La. neglectus lacked the ability to hinder L. humile resource exploitation, whereas the native La. niger did. These results suggest that La. niger could impact invasive populations of L. humile by interference competition, perhaps better so than some invasive species. While L. humile has become invasive in Southern Europe, the invasion process could be slowed down in the northern latitudes by such native dominant species.